Compression and permeability relationships in high water content clays - Berilgen, SA; Berilgen, MM; Ozaydin, IK (ELSEVIER, 2006)
Storing contaminant soils, such as dredge materials, sludge and mine tailings, and reclaiming contaminant soil storage areas back into the economy has arisen as an important economical and environmental problem in today's world. The scientific studies in the last thirty years have revealed critical new information regarding the deformation behavior of high water content soils. In this article relationships between material properties used in constitutive models for self-weight and/or surcharge loaded high water content (slurry) clays and their index properties are investigated. For this purpose three different kinds of clays in a slurry consistency are subjected to seepage induced consolidation in an experimental setup. Information obtained from these experiments, together with information already in literature, is used to investigate the relationships between the index properties and the consolidation constitutive model parameters. The relationships obtained from the experiments are then utilized to predict the self-weight consolidation of Halic (Golden Horn) dredge materials. These predictions are then compared with the results of numerical analysis and found to be in good agreement. (c) 2005 Elsevier B.V All rights reserved.
Keywords: clay; consolidation; compression; permeability; LINEAR CONSOLIDATION; SATURATED CLAYS; SLURRIES; Chemistry; Materials Science; Mineralogy